Analysis of Solidarity to Human Rights as Reflected in the Song Lyrics titled "Hear Your Call" by Sami Yusuf - Aa Qonaatun (Journal of English Language Teaching and Literature (JELTL), 2020)
This study try to analyze solidarity to human rights as reflected in the lyrics of the song entitled "Hear Your Call" by Sami Yusuf by using a sociological approach of literature. This study is a qualitative using content analysis method. The technique of study and data analysis is content analysis by identifying and interpreting the lyrics in the song, and then recognizes it as the data of study. Based on the analysis and discussion of song lyrics, it is concluded that there are 6 lines of song lyrics that contain of solidarity to human rights in the social, economic and cultural fields. Based on the sociology of the reader, it is concluded that the song is aimed to the reader or listener of the song, the lyrics contain the meaning and messages that want to influence their point of view and response after reading or listening to the song, and also expected to provide influence on the social conditions of victims in the flood disaster in Pakistan. The result of this study can be used as learning material in providing model of communicative English teaching through songs and also to support teaching materials in English Literature subject.